Tahap kepuasan pelajar terhadap kualiti pembelajaran dalam bidang pendidikan awal kanak-kanak di Kolej Universiti Islam Melaka: Level of student satisfaction on the quality of learning in the field of early childhood education at the University College of Islam Melaka - Mad Sehat, Syarinah; Asnil Aimi, Aziyati Zahirah; Damanhuri, Zaleha; Baharudin, Nur Syakira; Abd. Raof, Norjumira (Southeast Asia Early Childhood Journal, 2021)
Customer satisfaction is closely related to the quality of services received from certain sectors. For the education sector, students are recipients of services in the form of learning especially those provided by an institution. The quality learning process is of course closely related to the quality of the lecturers. However, student satisfaction with the quality of learning in the field of Early Childhood Education at Kolej Universiti Islam Melaka (KUIM) has not been seen. This study is important to implement because a student's success depends on the quality of a lecturer who can indirectly raise the image of an educational institution. This research was conducted to (i) identify the level of student satisfaction with the quality of learning in the field of Early Childhood Education at KUIM, (ii) identify the relationship between the quality of learning with the level of student satisfaction with the Early Childhood Education program and (iii) identify definitely a major factor contributing to student satisfaction levels. The survey study design was used by involving a total of 150 students from semester three to semester six using a questionnaire. The Google Form application is used to create the questionnaire and contains two parts, namely Part A (Demographic information) and Part B (Quality of learning). The results showed that the overall mean score value for the level of student satisfaction with the quality of learning in the field of Early Childhood Education was at a high level with a mean score value of 4.21 and a standard deviation of 0.59. Guidance factors contribute to the level of student satisfaction with the quality of learning. These results are supported by a moderate r value for each quality of learning. The findings of this study can be important for the lecturers as a guide in efforts to optimize the quality of Early Childhood Education at KUIM.